Colony density influences invasive and filamentous growth in Saccharomyces cerevisiae - Lucaccioni, A; Morpurgo, G; Achilli, A; Barberio, C; Casalone, E; Babudri, N (Folia microbiologica, 2007)
The effect of colony density on the dimorphic switch was determined in natural strains of Saccharomyces cerevisiae. In some strains invasiveness and pseudohyphal (PH) growth were highly sensitive to colony density; moreover, strains constitutively able to invade the substrate with PH formation positively influenced the invasiveness but not the PH growth of a different strain less prone to the dimorphic switch.
Keywords: Saccharomyces cerevisiae - proteiny; Saccharomyces cerevisiae; kultivační média; Saccharomyces cerevisiae Proteins; Culture Media; Hyphae; hyfy; regulace genové exprese u hub; Colony Count, Microbial; Gene Expression Regulation, Fungal; počet mikrobiálních kolonií